Potency of Cellulolytic Bacteria in Ulva lactuca from Ujung Genteng Beach, Sukabumi, Indonesia - Pari, Rizfi Fariz; Hardiningtyas, Safrina Dyah; Supraba, Ranula (Universitas Airlangga, 2023)
Fishery Ulva lactuca is a potential green seaweed species that causes green tides and has not been utilized. U. lactuca has the potency to attract cellulolytic bacteria due to its high carbohydrate content. U. lactuca is commonly found on the southern seacoast of Java Island, one of which is Ujung Genteng Beach, Sukabumi, Indonesia. In this research, we investigated the potential of cellulolytic bacteria from U. lactuca. Sources of bacteria are coming from the environment, the surface of the seaweed, and inside the seaweed (endophytes). To be able to determine the origin of the potential bacteria, the total plate count (TPC) was calculated with treatment without washing, washing with distilled water, and washing with a combination of distilled water and alcohol. From these bacteria, cellulolytic activity was tested using CMC media and morphological characterization. The most bacteria were found in the treatment without washing, as much as 7.48 Log Cfu/ml. The washing process reduced the TPC to 5.88 and 5.7 Log Cfu/ml in the treatment of washing with distilled water and washing with a combination of distilled water and alcohol, so that endophytic bacteria were obtained. The bacterial isolate with the highest cellulolytic potential was UW 1(1)1 5A1 from the non-washing treatment with a cellulolytic index of 2.25. These Gram-positive bacteria were in the form of filamentous lobates with a matte cream color with cocci-shaped cells. Meanwhile, the potential endophytic bacteria were Gram-positive coccus bacteria UW 3(1)1.2 with a cellulolytic index of 0.85. Both isolates have the potency to degrade cellulose.